Strategic Complementarities Between Innovation and Human Capital. The Neglected Role of Human Capital Demand - Aurora Amélia Castro Teixeira (Revista Brasileira de Inovação, 2004)
This study examines the conditions under which the demand for human capital is as (or more) important than the simple availability of educated or skilled human resources. The perspective taken is that it is the conscious and intentional attitude of firms, dependent, to a large extent, on respective strategies, that determines the demand for human capital, thereby conditioning the role of the latter in their performance. The automatic and linear character that many studies within the mainstream human capital theory assume is rejected here. Results, based on an in-depth study of fourteen Portuguese textile firms, reveal the "congruence" between firms behaviour towards human capital accumulation, characteristics of productive process and markets, and the omnipresent "fission" risk. New hirings of top skilled and educated individuals are seen as small contributors to firms (current) innovation capabilities. In contrast, existing top skilled and educated individuals are regarded as critical in this context. Este estudo analisa as condições em que a procura por capital humano é tão (ou mais) importante do que a simples disponibilidade de recursos humanos qualificados. É tomada a perspectiva de que é a atitude consciente e intencional das empresas, a qual depende em grande medida das suas estratégias, que determina a procura por capital humano, condicionando o seu desempenho econômico. Rejeita-se aqui o caráter automático e linear presente na maioria dos estudos associados à teoria do capital humano. Os resultados, baseados num estudo detalhado de 14 empresas têxteis portuguesas, revelam a “congruência” entre o comportamento destas relativamente à acumulação de capital humano, as características dos seus processos produtivos e mercados e a onipresença do risco de “cisão”. As novas contratações de indivíduos altamente qualificados são vistas como contribuindo pouco para as competências de inovação correntes das empresas. Em contraste, os atuais trabalhadores de altas qualificações são considerados essenciais nestes domínios.